Effect of coated-benzoic acid on growth performance, immunity, and intestinal functions in weaned pigs challenged by enterotoxigenic Escherichia coli - Qi, Jiawen; Yu, Bing; Hu, Youjun; Luo, Yuheng; Zheng, Ping; Mao, Xiangbing; Yu, Jie; Zhao, Xiaonan; He, Taiqian; Yan, Hui; Wu, Aimin; He, Jun (Frontiers in Veterinary Science, 2024)
IntroductionBenzoic acid (BA) could be added to the diets of weaned pigs to prevent diarrhea due to its antibacterial function. However, BA may be absorbed or decomposed before it can reach the hindgut. This study was conducted to explore the effect of a novel coated benzoic acid (CBA) on growth performance, immunity, and intestinal barrier functions in weaned pigs upon enterotoxigenic Escherichia coli (ETEC) challenge.MethodsIn a 21d experiment, 32 piglets were randomly assigned to 4 treatments: (1) a basal diet (CON), (2) CON added with CBA at 3  g/kg (CBA); (3) CON and challenged by ETEC (ECON); (4) CON added with CBA at 3 g/kg and challenged by ETEC (ECON). On d 22, all piglets were euthanised to obtain samples.ResultsDietary CBA supplementation elevated the average daily gain (ADG) of the ETEC-challenged pigs (p < 0.05). CBA also improved the digestibility of dry matter, gross energy, and ash (p < 0.05). Moreover, CBA elevated the ratio of blood basophil and the serum concentration of total cholesterol of the ETEC challenged pigs (p < 0.05). Importantly, CBA increased the serum concentrations of immunoglobulin A (IgA), IgG, and IgM (p < 0.05). CBA not only decreased the crypt depth but also increased the ratio of villus height to crypt depth (V:C) in the jejunum and ileum (p < 0.05). Moreover, CBA increased the activities of jejunal and ileal sucrase, and the activities of duodenal and ileal maltase (p < 0.05). Importantly, CBA elevated the expression levels of critical functional genes such as the claudin-1, occluding, glucose transporter-2 (GLUT2), and sodium/glucose cotransporter-1 (SGLT-1) in the jejunal epithelium upon ETEC challenge (p < 0.05). Additionally, CBA increased the abundances of total bacteria and Bacillus, and increased the concentrations of volatile fatty acids (acetic acid, propanoic acid, and butyric acid) in cecum (p < 0.05).DiscussionThese results suggested a beneficial role for CBA in alleviating intestinal injury in weaned pigs following ETEC challenge. Such effects may be tightly associated with elevated immunity and improved intestinal epithelium functions and microbiota.